Initial Investigation of the Blood-Brain Barrier in MS Lesions at 7 Tesla - Gaitán, María I. (Mult Scler, 2012)
BACKGROUND: We previously described two dynamics of contrast enhancement in scans of active multiple sclerosis lesions: Medium-sized, early lesions enhance centrifugally, whereas larger, slightly older lesions enhance centripetally. Due to technical limitations, our previous study did not characterize lesions < 5mm in diameter, cortical enhancement, and anatomical structures within lesions. OBJECTIVE: To obtain initial observations of these important aspects of lesion development on a 7 tesla scanner at high spatial resolution. METHODS: We scanned 8 patients, acquiring precontrast T2*-weighted scans, T1-weighted scans before and after contrast, and high-resolution dynamic contrast-enhanced scans during and up to 30min after contrast. RESULTS: We detected 15 enhancing lesions, obtaining dynamic data in 10. Five lesions < 4mm enhanced centrifugally (initial central enhancement expanded outward), and 5 lesions > 4mm enhanced centripetally (initial peripheral enhancement gradually filled the lesion). A leukocortical lesion initially showed enhancement in its white matter portion, which gradually spread into the cortex. 73% of lesions were clearly perivenular. CONCLUSION: Most active lesions are perivenular, and the smallest lesions enhance centrifugally. This supports the idea that lesions grow outward from a central vein.